Advanced genetic programming techniques for machine learning - A comparative analysis with state-of-the-art automated machine learning methods in the context of imbalanced binary classification - Frank, Franz Michael (2023)
Dissertation presented as the partial requirement for obtaining a Master's degree in Data Science and Advanced Analytics, specialization in Data Science